The political economy of targeting – a critical review. (November 2016) - Schüring, Esther; Gassmann, Franziska
Abstract : The political economy models of targeting postulate that going universal is a win‐win situation, for the poor and the middle class, as well as those who are in power. This article critically discusses the assumptions behind the political economy arguments of targeting and tests whether a universal mechanism is bound to politically excel in a low‐income country context. On the basis of attitudinal surveys with the urban, rural and student population in Zambia, we do not find any support for the predictions of the political economy models. We discuss the assumptions of the political economy models in the light of these findings and consider potentially decisive parameters that the models currently do not incorporate.